Topical Delivery of Diacetyl Boldine in a Microemulsion Formulation for Chemoprotection against Melanoma - Ahmed Al Saqr; Manjusha Annaji; Ishwor Poudel; Mohammed F. Aldawsari; Hamad Alrbyawi; Nur Mita; Muralikrishnan Dhanasekaran; Sai H. S. Boddu; Rabin Neupane; Amit K. Tiwari; R. Jayachandra Babu (MDPI AG, 2023)
This study aimed to develop a microemulsion formulation for topical delivery of Diacetyl Boldine (DAB) and to evaluate its cytotoxicity against melanoma cell line (B16BL6) in vitro. Using a pseudo-ternary phase diagram, the optimal microemulsion formulation region was identified, and its particle size, viscosity, pH, and in vitro release characteristics were determined. Permeation studies were performed on excised human skin using Franz diffusion cell assembly. The cytotoxicity of the formulations on B16BL6 melanoma cell lines was evaluated by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) assay. Two formulation compositions were selected based on the higher microemulsion area of the pseudo-ternary phase diagrams. The formulations showed a mean globule size of around 50 nm and a polydispersity index of <0.2. The ex vivo skin permeation study demonstrated that the microemulsion formulation exhibited significantly higher skin retention levels than the DAB solution in MCT oil (Control, DAB-MCT). Furthermore, the formulations showed substantially higher cytotoxicity toward B16BL6 cell lines than the control formulation (p < 0.001). The half-maximal inhibitory concentrations (IC50) of F1, F2, and DAB-MCT formulations against B16BL6 cells were calculated to be 1 µg/mL, 10 µg/mL, and 50 µg/mL, respectively. By comparison, the IC50 of F1 was 50-fold lower than that of the DAB-MCT formulation. The results of the present study suggest that microemulsion could be a promising formulation for the topical administration of DAB.